Tritium forms discrimination in ryegrass under constant tritium exposure: From seed germination to seedling autotrophy. (October 2017) - Renard, H.; Maro, D.; Le Dizès, S.; Escobar-Gutiérrez, A.; Voiseux, C.; Solier, L.; Hébert, D.; Rozet, M.; Cossonnet, C.; Barillot, R.
Abstract: Uncertainties remain regarding the fate of atmospheric tritium after it has been assimilated in grasslands (ryegrass) in the form of TFWT (Tissue Free Water Tritium) or OBT (Organically Bound Tritium). One such uncertainty relates to the tritium forms discrimination during transfer from TFWT to OBT resulting from photosynthesis (OBTphoto ), corresponding to the OBTphoto /TFWT ratio. In this study, the OBT/TFWT ratio is determined by experiments in the laboratory using a ryegrass model and hydroponic cultures, with constant activity of tritium in the form of tritiated water (denoted as HTO) in the "water" compartment (liquid HTO) and "air" compartment (HTO vapour in the air). The OBTphoto /TFWT ratio and the exchangeable OBT fraction are measured for three parts of the plant: the leaf, seed and root. Plant growth is modelled using dehydrated biomass measurements taken over time in the laboratory and integrating physiological functions of the plant during the first ten days after germination. The results suggest that there is no measurable discrimination of tritium in the plant organic matter produced by photosynthesis. Highlights: We study 3 H assimilation by ryegrass based on experimental and modelling approaches. Cultures are carried out in a hydroponic box with constant tritium activity level. The exchangeable fraction of OBT is determined for leaf and seed. The plant growth modelling is based on the transition from heterotrophy to autotrophy. The absence of measurable tritium forms discrimination in ryegrass is highlighted.